Hubungan Anemia Pada Kehamilan Dengan Kejadian Perdarahan Postpartum Di Puskesmas Patean Kabupaten Kendal Tahun 2022-2024 - Ika Tri Priantoro; Herlin Fitriani Kurniawati (CV. ITTC INDONESIA, 2025)
Postpartum hemorrhage is bleeding that occurs after the baby is born beyond normal physiological limits (<500 ml). In 2024 in Kendal Regency the maternal mortality rate reached 11 deaths, 4 deaths were caused by hypertension in pregnancy, labor and puerperium, 1 death was caused by post partum hemorrhage, 3 deaths were caused by other obstetric complications such as (Diabetes in/during pregnancy, labor and or puerperium, Liver disorders in pregnancy, labor, and or puerperium), 3 deaths were caused by non obstetric complications. The purpose of this study was to determine the relationship of anemia in pregnancy with the incidence of post partum hemorrhage that occurred at the Patean Health Center, Kendal Regency. The design in this research is quantitative approach method. The type of research in this study is an analytic study using the case control method with sample selection using total sampling technique obtained from medical records. The results of the Pearson Chi-Square Test on both variables showed a p value of 0.000, where 0.000 <0.05 so it can be concluded that there is a relationship between anemia in pregnancy and the incidence of postpartum hemorrhage. and the results of the contingency coefficient in this study were 0.552 can be stated as an indication of a fairly relevant relationship between the two variables in the analysis conducted. Pregnant women are expected to pay more attention to their pregnancy conditions by conducting routine ANC checks at least 6 times during pregnancy in order to detect and overcome health problems early.